Export citrus packaging and a study of the suitability of shooks produced from South African grown Pinus radiata and Pinus patula for this purpose - Bosman, D. L.(Daniel Lowne) (Stellenbosch : Stellenbosch University, 2012)
Thesis (DSc) -- University of Stellenbosch, 1963.